PEMBIAYAAN MURABAHAH BERMASALAH DAN MODEL PENYELESAIAN DI BMT UGT NUSANTARA CAPEM TEGALDLIMO - Habibulloh Habibulloh (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
This research is a qualitative research. which was held at BMT UGT Nusantara. This study aims to determine the application of murabahah financing risk management applied by BMT UGT Nusantara. While the data collection method in this study used interviews, and documentation information to obtain documents about the management of problematic financing. The data analysis methods used were interview, observation and documentation techniques. The results of the qualitative research show that the risk management system for problematic murabahah financing is to adjust or implement what is in the SOP (Standard Operating Procedure), the factors that affect non-performing financing are internal factors including employee negligence, etc., external factors include a decrease in customer income. , was hit by a disaster, and Efforts were made to save the problematic murabahah financing by using R3 (Rescheduling, Reconditioning, Restructuring) by carrying out predetermined procedures.